Bahasa Inggris - Firdayani, Chindy Fitri; Zainal, Sari Lestari; Sayuti, Jalaludin (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
The purpose of this observation is to analyze the influence of Lake Rayo festival event dimension on tourists' decision to visit. The quantitative approach is used by distributing questionnaires as a data-gathering tool. Population of these observations is tourists who have visited the Lake Rayo Festival within three years. This sampling method uses purposive sampling with 115 samples. Data analysis technique based on multiple linear regression analysis with the help of SPSS 22 vers. The proceed of observations reveal lest tourist decisions can be influenced by the dimensions of hospitality and symbolism. Meanwhile, it can be revealed that the dimensions of uniqueness, authenticity, theming, and festive spirit do not drive the decision to visit. The coefficient of determination shows that these variables can explain 60.9% of the variation in the decision to visit. Meanwhile, the rest is impacted by other factors not discussed of this observation. Event organizers are advised to continue improving these elements through authentic cultural presentation, event innovation, festive atmosphere, friendly service, and strong and meaningful symbolism. In addition, periodic research and evaluation are also important to understand visitor trends and preferences to improve the quality of future events. Therefore, to increase the attractiveness and success of the event in the future, organizers need to pay attention to and implement the suggestions provided based on the findings of this study.